Income Smoothing Drivers: Evidence from Indonesian Heavy Construction & Civil Engineering Sector - Ningrum, Kania; Kusumawardhani, Aninditha Putri; Putra, Okta Eka (Indonesian Scientific Publication, 2025)
This study investigates the influence of Cash Holding and Financial Leverage, as measured by the Debt to Asset Ratio (DAR), on the practice of Income Smoothing among infrastructure companies in Indonesia. Specifically, it focuses on firms operating in the heavy construction and civil engineering sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Employing a quantitative research approach with both descriptive and verification methods, the study examines a total population of 125 financial statements and annual reports from 25 companies over a five-year span. Through purposive sampling, 40 financial reports from 8 selected companies were analyzed to explore patterns and relationships between financial behavior and earnings management practices. The findings aim to provide insight into how liquidity and leverage decisions may relate to managerial efforts to stabilize reported earnings within the capital-intensive infrastructure sector.